Revealing the Teacher’s Role that Reflected KHD’s Principle in Freedom Writer Movie - Mufida Nadira Yuni Pureka Mufida (Journal of English Language Teaching and English Linguistics, 2023)
This study aims to determine teachers’ role of the main character of the movie.It discussed about teacher’s role that related with khd’s principle especially about Tut Wuri Handayani as found out in freedom writer movie. The object of this study was a freedom writer movie. The researcher choose this film because it really displays good moral values about education especially to the main character’s role .Descriptive qualitative method used in the data analysis while the method of observation was used to collect the data. The instruments of the study were the data from the script movie. This discussions were summarized to achieve the purpose of the study. The writer distinguished data through two categories Firstly, Tut Wuri means giving support and following from behind. Secondly, Handayani means giving moral encouragement. This result showed that main character did some techniques and strategies in teaching learning process that reflected khd’s principle. Main character showed the creativity of strategy in learning process. It because to encourage students comfort and serious during the activity of learning. Education as a dominant moral value that found this movie.